The Impact of the Seven Years War in the Arabian Gulf Region 1756-1763 - Al-Dulaimi, Yousif Sami Farhan Hussein (Al-Adab Journal, 2021)
The Seven Years War (1756-1763) greatly affected the Arab Gulf region, as the region witnessed a major British-French rivalry, and several clashes between ships, and the Arab Gulf region was the scene of military operations between the two countries, which prompted Britain to search for areas A safe alternative for fear of repeated French attacks on its commercial agencies, the last of which was the transfer of the British agency to Basra, which provided an alternative place for Britain, and a safe way for trade and mail to Europe, and thus the Seven Years War revealed the importance of the Arab Gulf region for Britain and France.